Academic Resilience, Cognitive Load, and Psychological Well-Being of Students Memorizing the Qur’an: A Case Study at a Private Islamic Religious University in Lampung - Ahmad Dawam; Sabanul Yamin (CV. Edujavare Publishing, 2026)
Role status double student Al-Quran memorizers ( tahfidz ) at the Lampung Private Islamic Religious College (PTKIS) triggered indication problem in the form of burden cognitive cognitive overload , mental fatigue ( academic burnout ), and degradation welfare psychological well - being research qualitative designed studies multi-case This aim analyze dynamics adaptation psychological and mechanism formation resilience academics in 16 students tahfidz in four PTKIS in the agrarian region of Lampung. Data collection was carried out through interview in- depth discussion group focused (FGD), observation, and study documentation, which is further analyzed use technique thematic cross case. Research results indicate that congestion memory work (working memory bottleneck), anxiety academic, as well as spiritual guilt as a result damage memorization can reduced in a way significant through integration coping cognitive -spiritual. Mechanism This covers reorganization intention (cognitive reframing), installments memorization (chunking), resignation active (tawakkal), and strengthening support peers (peer-support halaqah). By practical, proposed recommendation real in the form of restructuring friendly PTKIS curriculum cognition as well as provision center service counseling integrated mental health for student memorizing the Quran.